Temperature and Time Dependence of Elemental Segregation at Stacking Faults in Ni- and Co-Base Superalloys - Karpstein, Nicolas; Wu, Mingjian; Bezold, Andreas; Neumeier, Steffen; Cormier, Jonathan; Spiecker, Erdmann (Minerals, Metals and Materials Series, 2024)
Elemental segregation at stacking faults in the γ′ phase is a crucial part of the stacking-fault-based deformation of superalloys, and the local composition of a stacking fault critically affects the resistance of γ′ to further shearing. Here, the process of elemental segregation at extrinsic stacking faults in γ′ is examined in Ni-base superalloy CMSX-4 and Co-base superalloy ERBOCo-4. By measuring fault compositions not only after deformation, but also after additional load-free annealing steps of different durations and temperatures between 700 and 900 °C, time- and temperature-dependent aspects of the segregation process are revealed. It is shown that elemental segregation continues to evolve toward an equilibrium composition after a fault has formed, indicating that fully formed stacking faults still provide a driving force for segregation processes and that their equilibrium composition can differ from that which they obtain during their formation. As the elemental segregation process is diffusion-based, it is observed to be considerably slower at a lower temperature. In both alloys, the segregation trends observed after annealing depend on the annealing temperature: A lower temperature promotes a more γ-like fault composition associated with γ′ softening; conversely, at higher temperatures, the fault composition tends toward that of the η phase, which is considered beneficial in the context of local phase transformation strengthening. As η-like segregation also involves the enrichment of slowly diffusing tungsten, kinetics likely play a role in the observed temperature dependence.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Ni/Co-base superalloys; Phase transformation strengthening; Segregation; Stacking faults; Transmission electron microscopy